Analisis Komparatif Kebijakan Pemisahan (Spin -Off) Unit Usaha Syariah di Indonesia dan Malaysia - Putra, Dandi Riskia (Pusat Kajian Hukum Perbankan Fakultas Hukum Universitas Jember, 2024)
This study focuses on a comparative analysis of the separation (spin-off) policies of Islamic business units in Indonesia and Malaysia, two countries with significant developments in the Islamic banking and finance sector in Southeast Asia. This research employs a normative juridical method with a legislative and conceptual approach to examine various legal and operational aspects of the Islamic business unit separation policy. The findings reveal significant differences in the implementation and impact of the spin-off policy in both countries. In Indonesia, the separation is triggered by the achievement of a certain asset proportion by the Islamic Business Unit (UUS) relative to its parent Conventional Bank (BUK), while in Malaysia, the focus is more on strengthening the operational independence of Islamic banks. This research provides a deep understanding of how this policy affects the structure and performance of the Islamic banking sector in both countries, as well as its implications for the development of the Islamic economy in the region.